2023
DOI: 10.29136/mediterranean.1176976
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ willingness to pay for organic beans in southwest Nigeria: towards food safety

Abstract: Minimizing the health dangers associated with consuming inorganic staple food crops due to residues from pesticide and herbicide usage is a reasonable pathway to ensure nutrition security. Therefore, an extensive knowledge of consumers’ interest in organic foods would be a useful complementary strategy to public health interventions. This study examines consumers’ willingness to pay for organic beans in southwest Nigeria. Primary data were collected from 180 shoppers of beans. The data were analysed with descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These studies report that food safety and the attitude towards healthy eating are especially important when there are health concerns and the introduction of unfamiliar technology [21]. However, WTP for food safety depends on various factors, including food values, knowledge (awareness) [22,[25][26][27], and social, economic, and demographic characteristics [27,28]. For example, Ref.…”
Section: Consumer Preference and Wtp For Food Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…These studies report that food safety and the attitude towards healthy eating are especially important when there are health concerns and the introduction of unfamiliar technology [21]. However, WTP for food safety depends on various factors, including food values, knowledge (awareness) [22,[25][26][27], and social, economic, and demographic characteristics [27,28]. For example, Ref.…”
Section: Consumer Preference and Wtp For Food Safetymentioning
confidence: 99%
“…They found that even though female consumers are paying less for tomatoes, they are WTP significantly more for organic and inspected tomatoes. Other studies found age, knowledge, education, and income to have a significant influence on consumer WTP for organic and healthier products [6,27,30]. For example, Ref.…”
Section: Consumer Preference and Wtp For Food Safetymentioning
confidence: 99%
See 2 more Smart Citations